2002
DOI: 10.1161/01.res.0000014825.71092.bd
|View full text |Cite
|
Sign up to set email alerts
|

Prourokinase Mutant That Induces Highly Effective Clot Lysis Without Interfering With Hemostasis

Abstract: Abstract-Prourokinase (proUK) is a zymogenic plasminogen activator that at pharmacological doses is prone to nonspecific activation to urokinase. This has handicapped therapeutic exploitation of its fibrin-specific physiological properties. To attenuate this susceptibility without compromising specific activation of proUK on a fibrin clot, a Lys3003 His mutation (M5) was developed. M5 had a lower intrinsic activity and, therefore, remained stable in plasma at a 4-fold higher concentration than did proUK. M5 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
(42 reference statements)
0
26
1
Order By: Relevance
“…The sample size of this trial was only 41 which was insufficient to statistically analyse MACE events. As a new thrombolytic drug with fibrin‐selective speciality, prourokinase can be converted into active urokinase and produce thrombolytic effects . PROACT II study has confirmed that intra‐arterial prourokinase can increase recanalization rate without increasing hemorrhagic risk, suggesting prourokinase a safe and effective drug for thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size of this trial was only 41 which was insufficient to statistically analyse MACE events. As a new thrombolytic drug with fibrin‐selective speciality, prourokinase can be converted into active urokinase and produce thrombolytic effects . PROACT II study has confirmed that intra‐arterial prourokinase can increase recanalization rate without increasing hemorrhagic risk, suggesting prourokinase a safe and effective drug for thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…As a new thrombolytic drug with fibrin-selective speciality, prourokinase can be converted into active urokinase and produce thrombolytic effects. 17,18 PROACT II study has confirmed that intra-arterial prourokinase can increase recanalization rate without increasing hemorrhagic risk, suggesting prourokinase a safe and effective drug for thrombolysis. A Meta-analysis in China has also demonstrated that intravenous administration of prourokinase can improve recanalization rate, decrease MACE events and hemorrhagic complications.…”
Section: Hemorrhagic Complications and Mace During The Follow-upmentioning
confidence: 95%
“…Recombinant Lys300→His mutant prouPA expressed in Escherichia coli was obtained from Dr. Paolo Sarmientos at Primm (Milan, Italy) and prepared as previously described [8]. Recombinant prouPA expressed in E. coli was obtained from Landing Science and Technology Company, Nanjing, China.…”
Section: Methodsmentioning
confidence: 99%
“…M5 induced efficient, fibrin‐specific clot lysis in a plasma milieu in vitro and in dogs with venous thromboemboli, in which M5 was associated with no more bleeding than placebo [8]. In a more recent study of arterial thrombi in dogs, M5 and t‐PA induced comparably effective lysis, but blood loss from fresh hemostatic sites was tenfold higher with t‐PA, suggesting that M5 spared hemostatic fibrin.…”
Section: Introductionmentioning
confidence: 99%
“…These led to the development of a single site-directed (Lys300→His) prouPA mutant, M5, which was significantly more stable in plasma at therapeutic doses [18], [19], but otherwise retained the basic mechanism of action of prouPA. Two thrombolytic studies with M5 in dogs with venous or arterial thrombi showed that it was as effective as tPA but caused ten-fold less bleeding from injury sites [20], [21]. In the second of these studies, an unusual plasma inhibitor of two-chain M5 (tcM5) was identified which helped explain the low incidence of bleeding complications.…”
Section: Introductionmentioning
confidence: 99%